2001
DOI: 10.1128/jvi.75.2.988-995.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Bombyx mori Cytoplasmic Polyhedrosis Virus Genome Segment 4

Abstract: The complete nucleotide sequence of the genome segment 4 (S4) of Bombyx mori cytoplasmic polyhedrosis virus (BmCPV) was determined. The 3,259-nucleotide sequence contains a single long open reading frame which spans nucleotides 14 to 3187 and which is predicted to encode a protein with a molecular mass of about 130 kDa. Western blot analysis showed that S4 encodes BmCPV protein VP3, which is one of the outer components of the BmCPV virion. Sequence analysis of the deduced amino acid sequence of BmCPV VP3 revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Model of RNA Organization and Implications for Transcription Mechanism-CPV has a dsRNA genome of about 25 kb, consisting of 10 dsRNA segments with length ranging from 0.94 to 4.19 kb (27)(28)(29)(30)(31)(32). 2 As estimated from our reconstruction, the entire genome must be packaged within a volume of ϳ6 ϫ 10 7 Å 3 , corresponding to a concentration of RNA of ϳ500 mg/ml 2 S. Rao, K. Hagiwara, S. W. Scott, and G. R. Carner, GenBank TM accession number AF323784.…”
Section: Fig 4 Structures Of Proteins Involved In Transcriptionmentioning
confidence: 99%
“…Model of RNA Organization and Implications for Transcription Mechanism-CPV has a dsRNA genome of about 25 kb, consisting of 10 dsRNA segments with length ranging from 0.94 to 4.19 kb (27)(28)(29)(30)(31)(32). 2 As estimated from our reconstruction, the entire genome must be packaged within a volume of ϳ6 ϫ 10 7 Å 3 , corresponding to a concentration of RNA of ϳ500 mg/ml 2 S. Rao, K. Hagiwara, S. W. Scott, and G. R. Carner, GenBank TM accession number AF323784.…”
Section: Fig 4 Structures Of Proteins Involved In Transcriptionmentioning
confidence: 99%
“…The polyhedrin trimers are extensively cross-linked in polyhedra by noncovalent interactions and pack with an exquisite molecular complexity similar to that of antigen-antibody complexes (7). Because of the selectivity of the VP3 immobilization signal and the insolubility of polyhedra, just a simple rinsing and straining out of polyhedra can attain purification of the expressed proteins without any sophisticated purification step in solution (3,4). Unlike existing virus-like nanoparticles, polyhedra can be versatile nanocontainers that accommodate a wide range of cargos.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the exception of hematopoietic and/or blood cells, all single cells throughout the various organs receive their signaling cues from the extracellular matrix (ECM). 3 The basal lamina underlying the epithelial cell sheets and the specialized ECM in the mesenchyme, such as cartilage and bone, play a crucial role in this regard during the regulation of cellular behavior (1). The ECM provides a supramolecular architecture for the disposition of specific accessory molecules that exist in low abundance, such as growth factors, which are released after proteolytic cleavage to effect a downstream alteration in the behavior of the responding cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TP is encoded by genome segment 4 and was formerly known as VP3 or V3 in previous literature, but it was renamed to VP4 (i.e., the protein encoded by genome segment 4) for clarity (5,20). In addition to making up the turret/B-spike, VP4, and specifically its N-terminal segment (residues 1 to 79), was shown to "immobilize" foreign proteins onto the polyhedron (8,9), suggesting it may bind polyhedrin within polyhedra. A follow-up biochemical study further suggested the existence of a "polyhedrin recognition signal" within amino acid residues 42 to 93 that is sufficient to immobilize foreign proteins tagged by this fragment (7,13).…”
mentioning
confidence: 99%